The management of breakthrough cancer pain (BTCP) and the use of immediate release fentanyl products. Issue Volume 2:Issue (2012)Supplement 1 (1st March 2012) - Nwosu, Amara; Marley, Kate; Sulaivany, Esraa; Dickman, Andrew; Curie, Marie; Littlewood, Clare
Abstract : Background: Breakthrough pain is a common problem for people with cancer, and is associated with significant morbidity in these individuals. The association of palliative medicine (APM) has produced guidelines for the management of breakthrough cancer pain (BTcP). Immediate release fentanyl products are licensed for the management of BTcP; however, some practical concerns exist about their safety and routine use in clinical practice. Aims: (1) To identify the multi-disciplinary team (MDT) experience in managing BTcP in relation to APM guidance. (2) To identify the MDT experience of using immediate-release Fentanyl products in the management of breakthrough cancer pain. (3) To develop new regional guidelines to help health professionals manage breakthrough cancer pain. Methods: A literature review informed the development of two audit surveys which examined the health professional's experience of: (1) Managing a patient with BTcP. (2) Using short acting Fentanyl products. Electronic surveys were distributed to multidisciplinary members of four integrated cancer networks during the month of August 2011. Results: Twenty-eight BTcP surveys and 29 fentanyl products surveys proformas were completed. BTcP was identified correctly in most instances (80.8% of individuals had their background cancer pain controlled). Oxynorm was the most popular short-acting opioid (32% of occasions); Abstral was the most popular immediate-release Fentanyl preparation across hospice, hospital and community settings. Most episodes of BTcP were relieved in 30 min (56%). Concerns about storage and disposal (45%), delay in accessing medicines (45%), prescribing issues (62%) and education of generalists (62%) were highlighted by respondents. Conclusion: Most episodes of BTcP were correctly identified and pain tended to resolve within 30 min of receiving analgesia. Concerns around prescribing and the education of generalists were highlighted by respondents. The findings were presented and discussed at the Regional Specialist Palliative Care Audit Group Meeting. Local guidelines and standards were agreed for publication.